A new method for determination of the theoretical reduction amount for wide-thick slab during the mechanical reduction process - Wu C.-H.; Zeng J.-H.; Wu G.-R.; Xie X.; Zhang M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Mechanical soft reduction (MSR) is an effective method for elimination of the centerline segregation and porosity of the continuous casting steel slab, and the reduction amount is a key parameter that determines whether the MSR could be applied successfully. In the present work, a 2D heat transfer model was developed for predicting the non-uniform solidification of the wide-thick slab. The measured shell thickness by nail shooting experiment and the measured slab surface temperature by infrared camera were applied to validate the 2D heat transfer model. A new calculation method of theoretical reduction amount that could consider the influence of non-uniform solidification of the wide-thick slab was then derived. Based on the predicted temperature field by the 2D heat transfer model and the newly-proposed calculation method, the required theoretical reduction amount and reduction gradient/rate for the wide-thick slab were calculated and discussed. The difference between the newly-proposed method and the previous method, the influence of the casting speed and slab thickness on the required theoretical reduction amount and reduction gradient/rate were also investigated.